Are litter, plastic and microplastic quantities increasing in the ocean? - Galgani, Francois (2021)
Whilst both plastic production and inputs at sea have increased since the 1950s, several modelling studies predict a further increase in the coming years in these respective quantities. We compiled scientific literature on trends in marine litter, consisting largely of plastic and microplastics in the ocean, understanding that monitoring programs or assessments for these aspects are varied, frequently focusing on limited components of the marine environment in different locations, and covering a wide spectrum of marine litter types, with limited standardization. Here we discuss how trends in the amounts of litter in the marine environment can be compared with the information provided by models. Increasing amounts of plastic are found in some regions, especially in remote areas, but many repeated surveys and monitoring efforts have failed to demonstrate any consistent real temporal trend. An observed steady state situation of plastic quantities in many marine compartments and the fate and transport of plastic in the marine environment remain areas for much needed further research.